Sintesis dan Karakterisasi Komposit Silika Karbon dari Abu Bagasse (Ampas Tebu) - Muhammad Mufti Wibawa; Muhammad Athallah Rifqi Shafwan; Sutiyono (Jurnal Serambi Engineering, 2025)
Silica carbon composite is a mixture of polar inorganic silica and non-polar organic carbon. One of the applications of this composite is as an effective adsorbent, capable of absorbing metal ions. Bagasse ash is a material that contains a relatively high amount of silica. In this study, bagasse ash will be utilized as a constituent in the fabrication of silica-carbon composites. In this study, bagasse ash was extracted with NaOH at concentrations of 1N, 1.5N, 2N, 2.5N, and 3N. The filtrate from the extraction, in the form of Na2SiO3, will undergo dilution with demineralized water at a ratio of 1:1, 1:2, 1:3, 1:4, and 1:5. The variation in NaOH concentration and Na2SiO3 dilution ratio is designed to ascertain the impact of these conditions and conditions with the Si/C content most analogous to the optimum Si/C ratio. The findings indicated that the optimal silica carbon composite was achieved at a NaOH concentration of 1.5, with a silica content of 68.3% and a carbon content of 25.76%, resulting in a Si:C ratio of 2.65:1. In contrast, a NaOH concentration of 2N, with a silica content of 55.58% and a carbon content of 35.97%, yielded a Si:C ratio of 1.54:1. The results of the XRD analysis demonstrated that the silica carbon composite did not exhibit any crystalline phase peaks. Instead, a range of 15–30° was observed, with the highest peak located at 2θ = 30.1226°. This finding indicates that the silica carbon composite is amorphous.